Experimental analysis of horizontal liquid-gas slug flow pressure drop in d-type corrugated pipes - Naidek, Bruna P.; Kashiwakura, Lucas Y.; Alves, Rafael F.; Lange Bassani, Carlos; Stel, Henrique; Morales, Rigoberto E.M. (Experimental Thermal and Fluid Science, 2017)
Slug flows are commonly found in oil and gas offshore production operations, where pressure drop estimation is essential for facilities design. Several studies have been made to evaluate pressure drop for slug flows in smooth pipes. However, many offshore oil production lines consist of corrugated pipes, and the drag induced by the discrete cavities is rarely investigated for slug flows. For this purpose, an experimental flowloop was designed to measure pressure drop of air-water slug flows in 26 mm-ID corrugated pipes with four different groove geometries, consistent with the groove configurations used in offshore petroleum exploitation. The experimental data is regressed using the concept of pressure drop multipliers. Whilst this procedure is well established in literature for smooth pipes, an additional multiplier associated to the effect of the corrugated pipe on the pressure drop is proposed in this work. With such approach, a correlation for the pressure drop in horizontal liquid-gas slug flows in corrugated pipes is obtained by means of the groove geometry and the flow input data. Comparison of the proposed model predictions with experimental data shows ±7% accuracy.
Created from Fastlane, Scopus look-up
Keywords: Corrugated pipes; Experimental flowloop; Gas-liquid slug flow; Multiphase flow; Pressure drop correlation